(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study investigates the contemporary trends shaping the transformation of pedagogical methodology in the context of higher education internationalization. As universities worldwide pursue internationalization strategies, the pressure to align teaching methodologies with global standards has intensified, creating both opportunities and challenges for faculty in transitional education systems. Employing a convergent mixed-methods design, this research surveyed 320 faculty members and conducted semi-structured interviews with 45 education administrators across four universities in Uzbekistan to identify the nature, scope, and determinants of pedagogical transformation. Quantitative analysis revealed that 72.5% of respondents acknowledged the inadequacy of traditional lecture-centered instruction for internationalized programs. Five principal transformational trends were identified: competency-based education, blended learning integration, outcome-based education (OBE), transdisciplinary curriculum design, and digital pedagogical platforms. The study also identified four critical barriers to transformation: pedagogical mindset resistance, qualified faculty shortages, inadequate digital infrastructure, and standards misalignment. ANOVA analysis demonstrated statistically significant differences between international partnership universities and state universities across all transformation indicators (F(3, 316) = 8.72, p < 0.001). The findings provide an evidence-based framework for developing pedagogical transformation strategies in higher education systems undergoing rapid internationalization.